Uncertain litigation cost and seller behavior: Evidence from an auditing game - Ping Zhang; Bryan K. Church; Lucy F. Ackert (Federal Reserve Bank of Atlanta, 1998)
This paper reports the results of two experiments, each consisting of six sessions, designed to investigate difficulties that arise in estimating expected litigation costs in an auditing game. In each experimental session, the game consists of a series of periods in which sellers submit sealed offers to computerized buyers and, if hired, choose an effort level (low or high). The effort level affects the certain (direct) and uncertain (litigation) costs of performing the engagement. Across the two experiments, we vary the uncertainty surrounding the determination of the expected litigation cost. Our results strongly suggest that cognitive limitations hinder sellers' abilities to estimate total expected litigation costs. Across both experiments we observe a nontrivial number of suboptimal effort choices. Moreover, as the uncertainty of determining the expected litigation cost increases, the frequency of observed fee offers below the total expected cost of an engagement increases markedly.
Keywords: 330; Accounting